To study impact level of dominat parameters and propose estimate methodology for wave transmission efficiency of unconventional complex pile submerged breakwater - Tien, Nguyen Anh (Vietnam Journal of Marine Science and Technology, 2020)
This article proposes semi-empirical equations to estimate wave transmission coefficient through submerged complex with solid pile breakwater based on theories of random wave energy conservation of perpendicular wave transmission incorporated with physical hydraulic experiments in wave flume applied on both types of submerged breakwater with and without piles. These equations are able to describe interactions and energy dissipation process for each element of this complex structure which are foundation block and pile rows. Energy dissipation process depends on three major factors which are [relative submerge depth (Rc/Hm0), relative crest width (B/Hm0), wave slope at construction location (sm=Hm0/Lm)] and wave energy dissipation process through pile rows is determined by two major factors [relative submerged depth or submerged length of piles (Rc/Hm0), relative pile row width (Xb/Lm)].